2014
DOI: 10.1371/journal.pone.0112428
|View full text |Cite
|
Sign up to set email alerts
|

Spastin-Interacting Protein NA14/SSNA1 Functions in Cytokinesis and Axon Development

Abstract: Hereditary spastic paraplegias (HSPs) are a genetically diverse group of inherited neurological disorders (SPG1-72) with the cardinal feature of prominent lower-extremity spasticity due to a length-dependent axonopathy of corticospinal motor neurons. The most frequent form of autosomal dominant HSP results from mutations of the SPG4 gene product spastin. This is an ATPase associated with diverse cellular activities (AAA) protein that binds to and severs microtubules. While spastin participates in crucial cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 50 publications
(69 reference statements)
1
31
0
Order By: Relevance
“…and ). As previously reported, spastin exists in two major isoforms (spastin M1 and spastin M87 ) based on different translation initiation sites at residues 1 or 87 (Solowska et al .,), and spastin M87 is highly expressed in the neural tissue (Goyal et al ., ). We demonstrated that exogenous spastin protein exists in the cytoplasm as particles, which is consistent with a previous report (Roll‐Mecak and Vale, ; Finsterer et al ., ), and that spastin colocalizes with CRMP5 in the neurites and the cell bodies of neurons (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…and ). As previously reported, spastin exists in two major isoforms (spastin M1 and spastin M87 ) based on different translation initiation sites at residues 1 or 87 (Solowska et al .,), and spastin M87 is highly expressed in the neural tissue (Goyal et al ., ). We demonstrated that exogenous spastin protein exists in the cytoplasm as particles, which is consistent with a previous report (Roll‐Mecak and Vale, ; Finsterer et al ., ), and that spastin colocalizes with CRMP5 in the neurites and the cell bodies of neurons (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…SCOC was recently identified as a positive regulator of starvation-induced autophagy (58,59), presumably via its interaction with FEZ1 (fasciculation and elongation protein zeta 1), an inhibitor of the autophagy induction. SSNA1 is a putative coiled-coil protein and is involved in regulating cell division and cytokinesis as well as adult axonal development, presumably by interacting and modulating spastin, a microtubule-severing AAA ATPase (60). SCOC and SNNA1 were determined to interact with the 26S proteasome directly through a single cross-link with the coiled-coil region of Rpt6 respectively, i.e.…”
Section: Fig 5 Classification Of Human 26s Proteasomes Reveals Varimentioning
confidence: 99%
“…RNA-mediated knockdown of DIP13 resulted in a phenotype of multiflagellated and multinucleated cells, suggesting a cytokinesis defect. The mammalian DIP13 homolog, NA14, is a centrosomal protein the knockdown phenotype of which also results in cytokinesis defects (Goyal et al, 2014). The specific relationship between DIP13/NA14 and centrosomal function remains to be determined.…”
Section: Mutants That Affect the Spatial Coordination Of Cell Divisionmentioning
confidence: 99%